Pelatihan Public Speaking untuk Meningkatkan Kepercayaan Diri Siswa SMK di Era Digital - Helen Olivia; Risqi Inayah Dwijayanti; Achmad Budiman Sudarsono; Fitri Sarasati M; Solten Rajaguguk; Zhafira Athifah S; Iqbal Rocki Ulhaq; Burhanudin Yusuf; Muhammad Abdurrohim; M. Abdul Latief (Jurnal Pustaka Dianmas, 2026)
This community service activity aimed to improve the self-confidence and public speaking skills of vocational high school students in the digital era. The main problems faced by students included low self-confidence, anxiety when speaking in public, and limited understanding of effective communication techniques. The activity was conducted at SMK Muhammadiyah 9 Jakarta involving 80 students through a participatory approach consisting of lectures, discussions, demonstrations, and public speaking practice sessions. Evaluation was carried out through direct observation and performance assessment before and after the training. The results showed noticeable improvements across all assessed indicators. Students’ self-confidence increased from 45% to 80%, courage to perform in public increased from 40% to 82%, clarity of message delivery improved from 50% to 78%, speech organization increased from 48% to 75%, and nonverbal communication skills improved from 42% to 77%. These findings indicate that participatory and practice-based public speaking training effectively enhances students’ communication skills and self-confidence. The program is expected to contribute to the development of adaptive and communicative young generations who are better prepared for the demands of the digital era.